Case referrals to A.I.I.S.H. - Uma V (Journal of All India Institute of Speech and Hearing, 1972)
Until the First World War, it was not evident to the Otologists that functionallydeaf patients could exists. It has only been since World War I, when relativelylarge number of psychogenically deaf patients were reported by the Military ruralrehabilitation centres, that the suspicion or similar conditions existing in civilianpopulation arose